KEBUDAYAAN NGATIR DI CIPANAS Studi Fenomenologi pada Budaya Islam di C - Mumu Zainal Mutaqin (LPPM STAI La Tansa Mashiro, 2013)
This study is an attempt to understand and describe the phenomenon and the symptoms that occur on public ngatir Cipanas culture. The method used in this study is a descriptive analysis, this method is intended to describe the phenomenon of what is experienced by the research subjects. Techniques or approaches used in this study is a phenomenological approach. The results showed that Ngatir is concern that spawned the message that a Muslim should in addition be led to perform divine worship and practice their religion insaiyah. In addition, cultural traditions are created as custom ngatir using Islamic values Cipanas the population because they are followers of a religious Muslim who comply with state, tribal and religious.